(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article analyzes the phenomena of synonymy and antonymy in art terminology in the Uzbek and French languages. The article shows the connection between language and culture by studying synonyms and antonyms of important terms in the field of art. Examples of synonyms and antonyms of art terms in the Uzbek and French languages are given, which allows us to highlight the lexical richness, stylistic differences and cultural context of each language. The article also analyzes the diversity that occurs in the expression of works of art using synonyms and antonyms. The results obtained in the study help to identify the differences and similarities between the two cultures. In general, this study reveals the importance of art terminology from the point of view of linguistics and cultural studies.